ETHNOMATHEMATICS IN ARCHITECTURE: EXPLORING GEOMETRY AND PATTERNS IN THE WE TENRI OLLE TOMB - Naufal, Muhammad Ammar; Ja'faruddin, Ja'faruddin; Satrina, Satrina; Latif, Lhenny Ardillah; Novianti, Gita Eka; Risaldi, Risaldi; Muhammad, Fadhel; Hassan, Muhammad Nasiru (PATTIMURA UNIVERSITY, 2025)
This study explores the application of ethnomathematics in the We Tenri Olle Tomb, located in Pancana Village, Barru Regency, South Sulawesi. The study aims to identify mathematical concepts, particularly geometry, embedded within the tomb’s architectural elements. Using a qualitative descriptive method, data were collected through direct observation and literature review. The results show that the tomb's design reflects the application of planar geometry concepts, such as rectangular walls, and spatial geometry, such as a semi-spherical dome. Geometric transformations, including reflections on walls, translations in floral patterns, and rotations in window designs, were also identified. The tomb design embodies the dynamic cultural acculturation between the local Bugis culture and European colonial influences while symbolizing the diplomatic relationship between the Tanete Kingdom and the Netherlands. This study contributes to ethnomathematics by connecting cultural heritage with mathematical concepts and providing insights for developing culture-based mathematics education to enhance students’ understanding of geometry and appreciation for local traditions.